Obtenção de nanossílica funcionalizada visando o uso como aditivo em misturas cimentícias - Sousa, Ionara Pereira da Silva (2017)
The basic science on cements and concretes has incorporated research related to the understanding of the effects of the addition of nanosilica, and more recently functionalized nanosilicas, on the properties of cement pastes, mortars and concretes. In this context, the aim of this work was to prepare amino-functionalized nanosilicas from a commercial nanosilica (NS), provided as an aqueous colloidal suspension, by employing 3-aminopropiltrietoxissilano (APTS) as reactant, and to evaluate the characteristics of the samples. The functionalization reactions were performed in a biphasic system composed of dichloromethane and water, and employing different APTS/NS molar ratios. The materials were obtained as aqueous suspensions and their characteristics were evaluated at pH 4, 7 e 10. The functionalization of NS was evidenced by the presence of infrared bands associated to the aminopropyl group. Bands associated to silanol (-SiOH) and alcoxide (Si-OCH2CH3) groups were observed indicating that the hydrolysis and condensation reactions were not complete. The 29Si NMR signals of Si-C bonds confirmed the functionalization. The thermogravimetric curves indicated an increase of the amount of aminopropyl groups incorporated on NS as the APTS/NS ratio increased. Transmission electron microscopy images showed an increase in the mean particle sizes after functionalization. The aqueous suspended nanoparticles showed a positive zeta potential at pH 4 (+23 to +27 mV) and at pH 7 (+14 to +29 mV), indicating the presence of protonated amine groups. The zeta potential at pH 10 was weakly negative (-0.10 to -7,6 mV) for the samples prepared from the lower APTS/NS molar ratios (7.1 and 14.2 x 10-2), and still positive (+11 and +15 mV) for those prepared from the higher molar ratios (28.5 and 42.7 x 10-2), suggesting the existence of a higher amount of superficial amino groups within the latter. The mean hydrodynamic radius of the functionalized particles were greater (22 a 281 nm) than that of the NS (12 nm) at all pH values, with superior values for suspended particles at pH 10, particularly for samples prepared from the lower APTS/NS ratios. The amount of aggregates of bigger size (~100 to 2000 nm) was greater for samples prepared from the lower APTS/NS ratios. These variable characteristics are interesting for comparative studies involving the effects of the addition of these suspensions in cement pastes over the microstructure and properties of the resulting materials.